(untitled) (Advances in Applied Biological Research, 2026)
Heart failure continues to be a pandemic of the twenty-first century, a major contributor to which are chronic diseases and the increasing number of elderly people. The transition from the outdated “dropsy” to the modern neurohormonal theory of the illness is reviewed. Beta-blockers, MRAs, ARNIs, and SGLT2 inhibitors are the core “scaffold” of medicines that have improved nearly all patient outcomes, which is why treatment has revolutionized itself. However, since genetics recognizes the genetic variability of heart failure situations, it holds the key to the sector’s future. The goal of this effort is to identify illness endotypes for customized therapeutic care, driven by bioinformatics and multi-omics data. On top of that, the scientists are keen on implementing the same technology and in silico approaches to explore phytocomplexes with multitarget activity. AI and machine learning have dramatically transformed the pharmaceutical industry, disease prediction, and diagnostic procedures. This paper elucidates the evolution of heart failure management from an indiscriminate, reactive model to a tailored, systems-based, preventive paradigm.